Model Pemanfaatan air Hujan melalui Pemberdayaan Masyarakat di Kelurahan Wundudopi Kecamatan Baruga Kota Kendari: Rainwater Utilisation Model by Community Empowerment in Wundudopi Village, Baruga Sub-district, Kendari City - Bachrun, Ratna; Baskara, Surya; Wunantari, Wa Ode Arie; Bahrun, Ria Selfiyani; Santi, Santi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Rainwater Utilisation is one way of preserving and conserving water resources. At present, the use of groundwater is increasing without being accompanied by its sustainability. To maintain the availability of groundwater and to find alternative sources of water to meet daily needs, rainwater harvesting can be done by applying technology. This activity in Wundudopi Village, Baruga District, Kendari City aimed to provide understanding and explanation on the construction of biopore infiltration holes, infiltration wells, and rainwater harvesting. The practical method consisted of surveying and identifying the site, studying the problems, socializing, and making a rainwater harvesting model. Biopore infiltration holes and infiltration wells are used to facilitate the infiltration of rainwater into the soil, increasing groundwater reserves and reducing surface run-off. And rainwater harvesting as an alternative to supply daily water needs. With this community service, rainwater harvesting can be implemented in the domestic environment as a form of participation and responsibility for the availability and sustainability of water resources.